2022
DOI: 10.29333/iji.2022.15328a
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of E-Problem Based Learning on Students’ Interest, Motivation and Achievement

Abstract: The limitation of face-to-face meetings imposed by the Covid-19 pandemic has encouraged education environment to develop learning models with technology which can be integrated with Electronic-Problem-Based Learning (E-PBL). The study revealed whether the E-PBL Model, significantly affected (1) motivation, (2) learning interest, (3) achievemen, (4) motivation toward students' achievement, (5) learning interest toward students' achievement and (6) motivation toward students' learning interest in the entrepreneu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 12 publications
2
9
0
2
Order By: Relevance
“…The findings of this study support previous research that showed that the PBL model helps students be more active in the learning process in the classroom (Masek & Yamin, 2011;Munawaroh, Setyani, Susilowati, & Rukminingsih, 2022). Using conventional teachercentered learning models has proven less effective in improving students' critical thinking skills.…”
Section:  Results and Discussionsupporting
confidence: 81%
“…The findings of this study support previous research that showed that the PBL model helps students be more active in the learning process in the classroom (Masek & Yamin, 2011;Munawaroh, Setyani, Susilowati, & Rukminingsih, 2022). Using conventional teachercentered learning models has proven less effective in improving students' critical thinking skills.…”
Section:  Results and Discussionsupporting
confidence: 81%
“…Providing appropriate problem-based learning models, such as problem-based learning (PBL), in the learning process can improve student activity and learning outcomes. This model can increase the motivation of students to learn (Djonomiarjo, 2020;Munawaroh et al, 2022). The higher the learning motivation students have, the greater their chances of success in learning, so it can have a positive impact on the improvement of student learning outcomes (W. A.…”
Section: Analysis Of the Cognitive Results Of Studentsmentioning
confidence: 99%
“…A scientific attitude becomes an important point for improving student cognitive outcomes. Therefore, the problem-based learning model is the right solution for improving student learning outcomes (Munawaroh et al, 2022).…”
Section: Analysis Of the Cognitive Results Of Studentsmentioning
confidence: 99%
“…Online classes were facilitated by various online platforms such as Zoom, Google Classroom, email, etc. (Munawaroh et al, 2022). In this case, online learning has transformed people's way of thinking, attitudes, and behaviors to persist in teaching and learning activities during pandemic conditions (Chamberlain, 2020).…”
Section: Online Learning In Covid-19 Pandemicmentioning
confidence: 99%